A new methodology to obtain a corrected Bond ball mill work index valid with non-standard feed size. (October 2022) - Nikolić, Vladimir; Doll, Alex; Trumić, Milan
Highlights: Methodology for determining the corrected work index with non-standard feed size. The presented model is valid only for ores with a typical Hukki exponent. The presented procedure is not limited in terms of the use of a closing screen size. Abstract: The grindability of raw material is generally determined by Bond's standard ball mill grindability test (developed by the Allis Chalmers company). The ball mill grindability test is used for describing ore hardness and it is so widespread that the Bond Work Index generated from the test is often referred to as an ore characteristic. The ore resistance to grinding and energy consumption can be expressed using the work index and Bond's Third Theory. The Bond Third Theory method is widely used in the design of the grinding cycle, selection of grinding equipment, determination of required grinding power, and performance evaluation of the process. Despite widespread use for more than seventy years, doing a precise and complete Bond test can be challenging due to a variety of restrictions imposed by Bond. The initial size of the sample is strictly defined to be −3.35 mm. This paper describes the methodology for the determination of the Bond work index when coarse or fine raw material is found in the initial sample (i.e. when the initial sample not less than 3.35 mm).